Women and Media : a Critical Introduction. - Ross, Karen (John Wiley & Sons, 2007)
A cross-cultural examination of the ways in which women have worked inside and outside mainstream media organizations since the 1970s. This book provides an overview of the issues in feminist media critiques and interventions beginning with the literature in this growing field and ending with a study of women's media activism in 20 nations.